Cosmological functional renormalization group, extended Galilean invariance, and approximate solutions to the flow equations - Erschfeld, Alaric; Flörchinger, Stefan (Physical review, 2022)
The functional renormalization group is employed to study the nonlinear regime of late-time cosmic structure formation. This framework naturally allows for nonperturbative approximation schemes, usually guided by underlying symmetries or a truncation of the theory space. An extended symmetry that is related to Galilean invariance is studied and corresponding Ward identities are derived. These are used to obtain (formally) closed renormalization group flow equations for two-point correlation functions in the limit of large wave numbers (small scales). The flow equations are analytically solved in an approximation that is connected to the “sweeping effect” previously described in the context of fluid turbulence.